2018
DOI: 10.1016/j.exis.2017.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the oil boom on the lives of people living in the Albertine Graben region of Uganda

Abstract: We consider the impacts of the development of oil resources (exploration and extraction) on the lives and livelihoods of people living in the Albertine Graben region of Uganda. These impacts are both positive and negative and include: employment opportunities; infrastructure development; project induced displacement and resettlement; in-migration and influx; inflation; reduction of food security; restrictions on access to fishing, firewood and herbs for cooking and medicinal purposes; inadequate compensation; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 28 publications
0
32
0
Order By: Relevance
“…For example, a change to a Western diet, which usually accompanies the presence of new large projects in a region, can have grave consequences for Indigenous people's health, wellbeing, and social capital, due to the reduction in traditional food-related practices and associated social events [92]. Social impacts that are not properly managed can create serious long-term consequences for communities, including impoverishment, landlessness, homelessness, joblessness, marginalization and alienation, food insecurity, reduced health and wellbeing, loss of access to common property resources, social disarticulation, and impacts on sense of place [86][87][88][89][90][91][92][93][94][95][96][97]. Such impacts are often difficult to mitigate after they have occurred and can create irreversible long-term impacts, especially for Indigenous communities, which can, in extreme cases, arguably lead to genocide or ethnocide (the destruction of a particular culture and its way of living) [98].…”
Section: The Business Case For Respecting Community Rightsmentioning
confidence: 99%
“…For example, a change to a Western diet, which usually accompanies the presence of new large projects in a region, can have grave consequences for Indigenous people's health, wellbeing, and social capital, due to the reduction in traditional food-related practices and associated social events [92]. Social impacts that are not properly managed can create serious long-term consequences for communities, including impoverishment, landlessness, homelessness, joblessness, marginalization and alienation, food insecurity, reduced health and wellbeing, loss of access to common property resources, social disarticulation, and impacts on sense of place [86][87][88][89][90][91][92][93][94][95][96][97]. Such impacts are often difficult to mitigate after they have occurred and can create irreversible long-term impacts, especially for Indigenous communities, which can, in extreme cases, arguably lead to genocide or ethnocide (the destruction of a particular culture and its way of living) [98].…”
Section: The Business Case For Respecting Community Rightsmentioning
confidence: 99%
“…Uganda discovered commercially viable oil deposits in 2006 [1][2][3]. Studies have revealed both positive and negative expectations from the discovery of oil in the Albertine Graben region [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed both positive and negative expectations from the discovery of oil in the Albertine Graben region [4][5][6][7][8]. Many people are expecting that oil production will contribute to increased employment opportunities, higher incomes, improved roads, and improved access to public services [3]. However, the discovery of oil has also come with negative consequences for local people, including rent seeking, social conflict, and a local resource curse, which is similar to the experiences of other oil-producing countries [3,7,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations